2011
DOI: 10.1371/journal.pone.0027073
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Beta-Adrenergic Receptor Signaling by Trace Amine-Associated Receptor 1 Agonists

Abstract: Trace amine-associated receptors (TAAR) are rhodopsin-like G-protein-coupled receptors (GPCR). TAAR are involved in modulation of neuronal, cardiac and vascular functions and they are potentially linked with neurological disorders like schizophrenia and Parkinson's disease. Subtype TAAR1, the best characterized TAAR so far, is promiscuous for a wide set of ligands and is activated by trace amines tyramine (TYR), phenylethylamine (PEA), octopamine (OA), but also by thyronamines, dopamine, and psycho-active drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 87 publications
1
56
0
Order By: Relevance
“…However, we observe only minor differences in b-PEA EC50 for chimeras containing TM7 of rat Taar4 (Leu7.39), supporting the finding of Kleinau et al (2011) that this position cannot be assumed crucial for activation by b-PEA. It has been suggested that p-tyramine is probably binding to rat TA1 with its hydroxyl group engaged in hydrogen bond interactions with Ser5.46 (Tan et al, 2009).…”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…However, we observe only minor differences in b-PEA EC50 for chimeras containing TM7 of rat Taar4 (Leu7.39), supporting the finding of Kleinau et al (2011) that this position cannot be assumed crucial for activation by b-PEA. It has been suggested that p-tyramine is probably binding to rat TA1 with its hydroxyl group engaged in hydrogen bond interactions with Ser5.46 (Tan et al, 2009).…”
Section: Figuresupporting
confidence: 85%
“…49,Arg3.50,Glu6.30,Trp6.48,Pro6.50,Phe6.52). Furthermore, some ligands are recognized by both Taar and adrenoceptors (Kleinau et al, 2011), supporting a high conservation of the binding pocket.…”
Section: Figurementioning
confidence: 68%
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011). 3IT also tightly binds to the plasma protein apolipoprotein B-100 .…”
Section: E 3-iodothyronaminementioning
confidence: 74%
“…Pituitrin is an extract of bovine posterior pituitary hormones, oxytocin, and vasopressin [29] and izadrin is a medication used in the treatment of slow heart rate, heart block, and in rare situations, asthma [30]. Their combined effect causes decreased blood flow, limiting the supply of oxygen and glucose to tissues.…”
Section: Resultsmentioning
confidence: 99%